Social and economic efficiency degassing and methane production from coal seams in Kazakhstan - Karenov , R.S. (BUKETOV BUSINESS REVIEW, 2018)
It is emphasized that today's gas barrier, which faced the domestic coal industry, is generated by the use of high-performance mechanized complexes in coal mines. It is substantiated that it is possible to cope with such volumes of methane emissions only by the advance degassing of coal seams. It is noted that it has been practicing successfully in the Karaganda coal basin for several years. The opinion of industry experts that propose degassing works at all stages of development of coal deposits is generalized. It is shown that a systematic approach to solving this problem provides degassing of the seams during the construction of the mine with the use of degassing and ventilation means, as well as when it is closed. The main functional requirements for the degassing system are identified. It is concluded that they can be reduced to the following: maintaining in the lava physicochemical parameters of the air, ensuring the normal vital activity of the human body; prevention of the formation of explosive parameters in the atmosphere of the mine; reduction of pollution of the earth's atmosphere by harmful impurities emitted from coal seams; minimization of possible costs for the functioning of the system. Attention is paid to indicators of the effectiveness of the functioning of degassing of mines. It is proved that for degassing systems, the main indicator of its effectiveness is the degassing ratio, which is the ratio of the methane flow, given by the degassing system, to the total gas evolution at the site.